2004
DOI: 10.1063/1.1812817
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse nanoparticles via metal induced crystallization

Abstract: Articles you may be interested inPhotoluminescence properties and crystallization of silicon quantum dots in hydrogenated amorphous Si-rich silicon carbide films This paper discusses the self-assembled formation of monodisperse gold-rich nanoparticles and associated crystalline silicon nanostructures. Multilayer films comprising of amorphous Au 25 Si 75 and amorphous silicon were grown via dc magnetron sputtering and subsequently annealed under varying thermal conditions. The films were characterized by electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Such possibility has been demonstrated in both microscale 33,34 and nanoscale. 34,35 However, in our case the (111) Si texture is not clear from XRD, probably because the layer is too thin (<13 nm) and embedded with some <5 nm Au particles precipitated from annealing (Figure 6c). As a result, the (111) crystal Au nanoparticles, together with the thin Si layer (expected (111) crystallized after the annealing with Au), seed the growth of Si NWs into AE111ae orientation and vertical to the substrate.…”
Section: Lettermentioning
confidence: 58%
“…Such possibility has been demonstrated in both microscale 33,34 and nanoscale. 34,35 However, in our case the (111) Si texture is not clear from XRD, probably because the layer is too thin (<13 nm) and embedded with some <5 nm Au particles precipitated from annealing (Figure 6c). As a result, the (111) crystal Au nanoparticles, together with the thin Si layer (expected (111) crystallized after the annealing with Au), seed the growth of Si NWs into AE111ae orientation and vertical to the substrate.…”
Section: Lettermentioning
confidence: 58%
“…34 Also, Au nanoparticles have been shown to develop in just 30 minutes in a Si/Au system at 250 °C. 35 The size of the Au islands is similar on the Si micro-and nano-structured substrates since both had comparable amounts of Au deposited on their surfaces. Why then do the nanowires form exclusively on nanostructured substrates?…”
Section: Formation Of Silica Nanowires On Si Nanostructuresmentioning
confidence: 73%
“…This is vapor liquid solid (VLS) growth because of the presence of the liquid reservoir on top of the nanowire; here the reservoir is consumed during nanowire growth and therefore does not act purely as a catalyst. Unlike size selection by metal-induced crystallization or amorphization which results in 1-2 nm particles, 35 this mechanism relies on metal-induced oxidation, with the resulting nanosphere size being set by a combination of the thermodynamically-controlled oxidation rate and the Si/Au ratio.…”
Section: Formation Of Silica Nanowires On Si Nanostructuresmentioning
confidence: 99%
“…Earlier work has shown that amorphous Au x Si 100−x / Si sputtered multilayers, when annealed at 250°C, result in Au-rich nanoparticles and crystalline silicon nanowires. 11 Postanneal samples were oxidized using ultraviolet ͑UV͒-ozone oxidation. 12,13 This step was carried out by transferring samples from the deposition chamber into an in situ oxidation chamber where high-purity O 2 gas ͑99.999%͒ and UV light from a Hg lamp ͑wavelengths 185 nm and 254 nm͒ were introduced.…”
Section: Gold Nanoparticles Via Alloy Decomposition and Their Applicamentioning
confidence: 99%